Primary types of longhorned beetles (Coleoptera, Cerambycidae, Vesperidae and Disteniidae) of Southwest University (SWU) - Li, Zhu; Chen, Li (Zootaxa, 2020)
The primary types of longhorned beetles of Southwest University (SWU) are catalogued and figured. The original combination, current name, type locality, date and collector of type specimen are verified and presented. There are 69 holotypes and 86 paratypes in SWU. These 155 type specimens belong to three families, 51 genera, 71 species, of which 8 are in Disteniidae, 3 in Vesperidae, 3 in Prioninae, 12 in Lepturinae, 15 in Cerambycinae, and 30 in Lamiinae. A new synonym is proposed: Paraleprodera insidiosa (Gahan, 1888) = Paraleprodera bimaculata Wang & Chiang, 2000 syn. nov.